Pelatihan Aplikasi Komputer Akuntansi Zahir Accounting Versi 6 Untuk Peningkatan Kompentensi Akuntansi di SMKN 2 Kota Bekasi - Sri Yuli Ayu Putri; Dade Nurdiniah; Muhammad Muhammad; Ajran Febryan; Azizia Ramadhani Suci (I-Com: Indonesian Community Journal, 2025)
The purpose of this community service activity is to improve the accounting competence of SMKN 2 Kota Bekasi students using the Zahir Version 6 application and make it easier to prepare financial reports. Based on this, it is important to provide an understanding of the Zahir Accounting Application Version 6 for SMKN 2 Kota Bekasi students. This activity was attended by 15 teachers and 31 grade 12 students majoring in accounting. In this activity, the methods chosen were observation, consultation, socialization, evaluation and solutions. The final result of this training was an increase in the percentage of correct answers in the implementation of the pre-test and post-test as well as a level of partner satisfaction of 81% stating very satisfied and 19% stating satisfied.